719 Colovaginal Fistula from Neglected Vaginal Pessary; Fallouts from the COVID-19 Pandemic. (12th October 2021) - Oyewole, B; Elzaafarany, A; Tawfik, A; Campbell-Smith, T
Abstract: An 86-year-old lady was admitted with a one-week history of feeling unwell, polyuria, dysuria, urinary and faecal incontinence. She had previously been treated for recurrent UTIs by her GP. On examination she had suprapubic tenderness but no peritonism. Observations revealed tachycardia of 122bpm with a temperature of 36.3*C. Inflammatory markers were raised with a white cell count of 22.0x10 6 /L and CRP 129 mg/L. Urine cultures grew Pseudomonas aeruginosa. She was managed for urosepsis with intravenous antibiotics. Past medical history included vaginal pessary for uterine prolapse, congestive cardiac failure, hypertension, polymyalgia and osteoporosis She lived alone with no package of care. On admission she improved with intravenous antibiotics however she had a perineal examination due to ongoing faecal and urinary incontinence and was noticed to be passing faeces per vaginam. A colo-vaginal fistula was suspected, and she was reviewed by the gynaecologist who noted her pessary had been in-situ for up to a year and her routine appointment to have it changed was cancelled due to the COVID-19 pandemic. An MRI Pelvic scan confirmed a 3x2cm rectovaginal fistula. She was reviewed by the general surgery team and the decision was made for her to be defunctioned to prevent her episodes of recurrent UTIs and improve her quality of life. She successfully had a laparoscopic end colostomy with an uneventful post-operative period. This case highlights the harms caused from the cancellation of appointments and demonstrates a rare cause of rectovaginal fistula.